The assessment of the time allocated to the physical activity and food behaviour of a lot of adolescents from 2 highschools in Suceava - Adriana, Albu; IonuÅ£, Onose; Ecaterina, GrigoraÅŸ; Mihaela, HodorcÄƒ Raluca (Arena-Journal of Physical Activities, 2019)
In the framework of the external factors that influence the growth/development of the students, sports activity and alimentation play an essential role. Material and method: The study was conducted on a batch of 98 teenagers from 2 highschools in Suceava. They filled in a questionnaire with questions relating to the time allotted for physical activity and dietary habits. Results and discussion: in most cases the students allocated daily physical activity between 15 and 60 minutes (54.08%). The dominant contribution of milk is 2-3 times per week (31.63%) and chicken meat (51.02%). The result is unsatisfactory, which highlight the problems related to the consumption of food products of animal origin. Cooked vegetables are present in the menus especially 4-7 times (36.73%) and bread (72.44%). Conclusions: the time allotted for daily activities is pretty modest and the intake of animal origin products is low.